Postoperative management of heart failure in pediatric patients. (1st February 2016) - Yuerek, Mahsun; Rossano, Joseph W.; Mascio, Christopher E.; Shaddy, Robert E.
ABSTRACT: Low cardiac output syndrome (LCOS) is a well-described entity occurring in 25–65% of pediatric patients undergoing open-heart surgery. With judicious intensive care management of LCOS, most patients have an uncomplicated postoperative course, and within 24 h after cardiopulmonary bypass, the cardiac function returns back to baseline. Some patients have severe forms of LCOS not responsive to medical management alone, requiring temporary mechanical circulatory support to prevent end-organ injury and to decrease myocardial stress and oxygen demand. Occasionally, cardiac function does not recover and heart transplantation is necessary. Long-term mechanical circulatory support devices are used as a bridge to transplantation because of limited availability of donor hearts. Experience in usage of continuous flow ventricular assist devices in the pediatric population is increasing.